2000
DOI: 10.1007/s004240000327
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and fatigue-induced modification of function and proteins in intact and skinned murine diaphragm muscle

Abstract: Fatigue studies of isolated, intact muscles typically utilize solutions saturated with O2. However, under in vivo fatiguing conditions, less oxygen is delivered to the muscles and they actually experience hypoxia. No studies to date have correlated the effects of acute hypoxia on the isometric contractile properties of intact muscles, skinned fibers isolated from the same muscles, and the cellular content of specific muscle proteins. Therefore, we have studied the effects of in vitro acute hypoxia on the fatig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 30 publications
4
15
0
Order By: Relevance
“…After muscles were mounted, the resting tension and the stimulatory voltage (provided by a Grass digital stimulator) were adjusted to produce T max . In our recently published study [27], we found that the stimulatory frequency necessary to produce T max was 100 Hz. The stimulatory pulses for the experiment were computer-controlled by a PC (Pentium II) running a customized LABView 4.1 program that controlled the Grass stimulator, collected the digitized force, and analyzed all the data collected.…”
Section: Methodsmentioning
confidence: 97%
See 4 more Smart Citations
“…After muscles were mounted, the resting tension and the stimulatory voltage (provided by a Grass digital stimulator) were adjusted to produce T max . In our recently published study [27], we found that the stimulatory frequency necessary to produce T max was 100 Hz. The stimulatory pulses for the experiment were computer-controlled by a PC (Pentium II) running a customized LABView 4.1 program that controlled the Grass stimulator, collected the digitized force, and analyzed all the data collected.…”
Section: Methodsmentioning
confidence: 97%
“…Intact muscle preparation All experimental protocols were performed at room temperature (22±2°C) and followed protocols previously described by our research group [27]. Mice were killed by CO 2 inhalation and the intact diaphragm muscles were removed and placed in a dissecting dish containing a modified Ringer solution with the following composition (in mM): 142.0 NaCl, 5.0 KCl, 2.5 CaCl 2 , 2.0 MgCl 2 , 5.0 HEPES, 11 glucose, pH 7.35 (adjusted with NaOH), continuously bubbled with 100% O 2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations